The Rhône-Alpes Health Platform - Durand, T.; Spacagna, H.; Verdier, C.; Biron, P.; Flory, A. (Methods of Information in Medicine, 2007)
Objectives: The purpose of this workis to develop a health information platform connecting most health facilities in the Rhône-Alpes region. The health platform called SIS-RA is used through a Web interface. An iconic interface is dedicated to the platform and presents information in a unique way for all users.Methods: Newtechniques have been used to develop this platform which will be used by a great number of Rhône-Alpes doctors in the future. We chose a user-centered design which takes into account doctors’ requirements (hospital and GP). We also consider that no system has to be rebuilt, but a direct connection to the legacysystems should be provided.Results: The platform permits fast and more appropriate medical decisions than those made without this information system. The iconic interface presents all medical documents in a uniform way. Currently, 11 healthcare facilities and 15 community health networks are connected to SIS-RA sharing more than 60,000 records with 1.2 million indexed items. 3200 doctors use the system.Conclusion: The platform is approved by French supervision authorities (regional hospitals association (ARH)), regional practitioners union (URML) and Rhônes-Alpes region administration and is known as the official shared health record.
Keywords: Electronic medical record; medical interfaces; health platform